Position Controlled Growth of Single Crystal Cu3Si Nanostructures - Boland, John (My University, 2015)
In this work we demonstrate the position controlled growth of single Cu3Si nanostructures using a Ge-Cu bilayer film that contains a pattern of defects on a Si substrate with a thin oxide layer. The defects act as nucleation centres for growth whilst the presence of Ge within the bilayer is critical to insure effective surface diffusion rates and to eliminate spurious nucleation and growth. This behaviour presented is consistent with a surface energy driven growth mechanism. The defect mediated reaction between Cu and the underlying Si substrate insures that the grown nanostructures are in perfect registry with the substrate. The possible applications and alternative implementations of this technology are discussed.
Keywords: Cu3Si; surface energy driven growth (SEDG); Eutectic; patterning